The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/978-3-319-29360-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Applying Grover’s Algorithm to AES: Quantum Resource Estimates

Abstract: Abstract. We present quantum circuits to implement an exhaustive key search for the Advanced Encryption Standard (AES) and analyze the quantum resources required to carry out such an attack. We consider the overall circuit size, the number of qubits, and the circuit depth as measures for the cost of the presented quantum algorithms. Throughout, we focus on Clifford+T gates as the underlying fault-tolerant logical quantum gate set. In particular, for all three variants of AES (key size 128, 192, and 256 bit) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
230
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(242 citation statements)
references
References 25 publications
(31 reference statements)
1
230
0
1
Order By: Relevance
“…Although it is difficult to estimate the cost of a physical implementation which does not yet exist, we can compare security levels as quantum operation counts in this model. For example, Grover search of the secret key for AES-128 is known to require approximately 2 64 quantum evaluations of the cipher, and 2 84 quantum operations [21].…”
Section: The Quantum Circuit Modelmentioning
confidence: 99%
“…Although it is difficult to estimate the cost of a physical implementation which does not yet exist, we can compare security levels as quantum operation counts in this model. For example, Grover search of the secret key for AES-128 is known to require approximately 2 64 quantum evaluations of the cipher, and 2 84 quantum operations [21].…”
Section: The Quantum Circuit Modelmentioning
confidence: 99%
“…Random statistics of the target function are carefully handled which lead to increase in iteration number compared with the case of unique target. Surprisingly, however, the cost of dealing with random statistics in this paper is not expensive compared with the previous work [27] under single processor assumption. Furthermore, when processor parallelization is considered, we observed that this extra cost gets even more negligible.…”
Section: This Workmentioning
confidence: 89%
“…AES Key Search. Grassl et al reported the quantum costs of AES-k key search for k ∈ {128, 192, 256} in the units of logical qubit and gate [27]. In estimating the time cost, the author's focus was put on a specific gate called 'T' gate and its depth, although the overall gate count was also provided.…”
Section: Quantum Resource Estimatesmentioning
confidence: 99%
“…Note however that such complexity results are currently unproven, and may be weakened by technological progress. For instance, Shor's algorithm and quantum computing are effective for integer factorization [1], Grover's algorithm and quantum computing can be used against AES [2], and memcomputing has been proved to be effective to solve subset sum [3].…”
Section: Introductionmentioning
confidence: 99%